“Nothing on Earth Passes without a Trace...” - E. V. Abramovskikh (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The review of unique “memorial” edition “Life of Remarkable People of Physical and Mathematical Faculty” devoted to genesis and main stages of formation of physical and mathematical school in Samara (Samara State Socio-Pedagogical University) is presented. A detailed analysis of the presented material is made, which covers almost a century-old history of the physical and mathematical school, from the 1930s until today. Attention is focused on the composition of the book, reflecting its main idea: to show the continuity of generations and the importance of each teacher both as a person and as a scientist, as well as a teacher who contributed to the development of the scientific school.